Обробка потоків інформації зі ЗМІ для ідентифікації цільових інформаційних конструктів - Олексюк, Олексій Іванович (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
Nowadays variety of the feasible communications is constantly increasing due to the rapid ICT development. An average person is under the pressure of massive information flows from news media, information agencies, social networks, messengers etc. regularly and this pressure has escalated since the Ukrainian war started. The study presents the results of the development of a coherent approach to processing or analysing information from different media sources by employing machine learning models and data mining techniques. The definition in the study is “an information construct” that is an information structures with the following attributes: artificial, goal-oriented, structured and perceived. Information has become not only a resource for economic activity but also a weapon for different political groups, military forces etc.